In‐silico investigations of dynamic mechanical behavior of Bombyx mori silk fibroin nanostructure under cyclic deformations and associated molecular mechanisms. Issue 20 (23rd July 2022) - Patel, Mrinal; Singh, Satinder Paul; Dubey, Devendra K.
Abstract: Bombyx mori silk fibroin (SF) is a prospective biomaterial for application in tissue engineering. As biomaterial for functional tissue such as bone and cartilage, the tissue grafts undergo cyclic loading similar to native tissues. An important factor in designing the SF based tissue grafts is understanding the dynamic mechanical behavior and underlying molecular mechanisms in B . mori SF at various length scales, which in turn requires an understanding of the nanoscale mechanics of B . mori SF. Dynamic mechanical behavior of B . mori SF nanostructure under varying hydration conditions has been investigated in the present study. For this purpose, molecular dynamics simulations for stress relaxation tests and strain‐controlled cyclic deformations for three separate strain amplitudes are performed for B . mori SF atomistic models. Results show that B . mori SF exhibits viscoelastic behavior. Analysis of obtained hysteresis loops (shape, size, area and inelastic strain values) shows an increase in viscous behavior of B . mori SF nanostructure with increase in hydration levels and strain amplitude levels, along with a mostly recoverable deformation with little effect of strain history. The analysis also shows that non‐bonded interaction and bond angle energies have a dominating role in governing the viscoelastic behavior of B . mori SF. Abstract :